José Agostinho Baptista, Caminharei pelo Vale da Sombra, José Agostinho Baptista, Lisboa, Assírio & Alvim, 2011. - Santos, Thierry Proença dos (Limite. Revista de estudios portugueses y de la lusofonía, 2022)
recensión